2017
DOI: 10.5937/industrija45-12978
|View full text |Cite
|
Sign up to set email alerts
|

The impact of tax forms on economic growth: Evidence from Serbia

Abstract: The aim of the paper is to show the relevance of nexus between tax forms and economic growth and how they affect on gross domestic product in Serbia for the period 2006-2015. The impact is manifested through the analysis of three main tax forms: personal income tax (PIT), corporate income tax (CIT) and value-added tax (VAT) and their effect on the macroeconomic indicator as gross domestic product (GDP

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
(38 reference statements)
0
3
0
4
Order By: Relevance
“…Andrašić et al (2018) showed that 1% increase of tax revenue enhances the gross domestic product for 0.29% in OECD countries from 1996 to 2016. Kalaš et al (2017) confirmed a significant correlation between taxes and economic growth in Serbia meausred by gross domestic product growth rate. Szarowska (2013) identified significant and positive implications of indirect taxes on gross domsetic product growth rate in European Union for the period 1995-2010.…”
Section: Literature Reviewmentioning
confidence: 54%
See 1 more Smart Citation
“…Andrašić et al (2018) showed that 1% increase of tax revenue enhances the gross domestic product for 0.29% in OECD countries from 1996 to 2016. Kalaš et al (2017) confirmed a significant correlation between taxes and economic growth in Serbia meausred by gross domestic product growth rate. Szarowska (2013) identified significant and positive implications of indirect taxes on gross domsetic product growth rate in European Union for the period 1995-2010.…”
Section: Literature Reviewmentioning
confidence: 54%
“…There are many empirical studies that have estimated tax revenue and gross domestic product (Anastassiou and Dritsaki;2005;Belullo and Dužman, 2011;Castro and Ramirez Camarillo, 2014;Kalaš et al, 2017;Loganathan et al, 2017;Stoilova, 2017;Andrašić et al, 2018;McNabb, 2018). Anastassiou and Drtiskai (2005) examined the relationship between tax revenue and gross domestic product in Greece for the period 1965-2020 and their empirical findings confirmed existence of causality between these variables in the observed period.…”
Section: Literature Reviewmentioning
confidence: 89%
“…Da bi se uporedila visina i nivo ovog poreskog oblika u Srbiji, to uključuje i prosečnu stopu PDV-a u zemljama EU. U periodu 2005-2010. stopa PDV-a je niža za 1,5% -2,5% od prosečne stope PDV-a u EU (Kalaš & Milenković, 2017). Iako je Srbija povećala stopu od 18% do 20%, ona je i dalje ispod proseka EU što se može videti i na grafikonu 1.…”
Section: Uloga I Terminološka Klasifikacija Poreza Na Dodatu Vrednostunclassified
“…Iako je Srbija povećala stopu od 18% do 20%, ona je i dalje ispod proseka EU što se može videti i na grafikonu 1. Mora se istaći, da je stopa Svaka zemlja traži načine za povećanje prihoda i to je omogućilo mnogim ekonomijama da uvedu PDV na robu i usluge (Kalaš & Milenković, 2017). Bitno je istaći da ova vrsta poreza ima značajan uticaj na visinu javnih prihoda u budžetu Republike Srbije.…”
Section: Uloga I Terminološka Klasifikacija Poreza Na Dodatu Vrednostunclassified
“…The estimates of natural resources rents are calculated as the difference between the price of a commodity and the average cost of producing it. This kind of taxation contributes to the GDP to a different extent (Kalaš et al, 2017). This is done by estimating the world price of units of specific commodities and subtracting estimates of average unit costs of extraction or harvesting costs (including a normal return on capital).…”
Section: Total Natural Resources Rentsmentioning
confidence: 99%